Disponibilidade hídrica no cultivo de cravina em vasos com substrato de cinza de casca de arroz - Schwab, Natalia Teixeira (2011)
The aim of this study was to analyze the development of cravina culture in substrate ash rice husk in different vessel sizes and under varying levels of water availability, observing its response as the height of the stems developed, number of nodes per stem; fresh weight and dry weight of stems and number of flower buds developed per stem. The cultivar used in the experiment was a hybrid of series 'Melody', the seedlings were obtained by cutting a die makers deployed specifically for this purpose. The seedlings were first planted in rooting where they remained for 30 days and were then transplanted in black plastic pots, 8 and 18 liters, filled with a substrate of rice husk ash, and kept 100% 80% 60% and 40% of the capacity of water retention of the vessels. Maintenance of the water vessel was performed by the method of weighting, with added amounts of water to keep the vessel in your weight limit. The water consumption of plants was determined by the method of weighing over two crop cycles. Results showed that the water consumption of this species is highly influenced by the weather; is recommend the use vessel of lower capacity and maintenance water in 40% of the capacity to retain water; it is preferable to growing the cravina in just a cycle, since the rods obtained in the second exhibit features not fit for commercialization.